Effects of Olopatadine Hydrochloride, a Histamine H1 Receptor Antagonist, on Histamine-Induced Skin Responses - Ishii, Norito; Hashimoto, Takashi; Hamada, Takahiro; Dainichi, Teruki; Karashima, Tadashi; Nakama, Takekuni; Yasumoto, Shinichiro (Dermatology Research and Practice, 2010)
Effects of olopatadine hydrochloride, a histamine H1 receptor antagonist, on histamine-induced skin responses were evaluated in 10 healthy subjects in comparison with placebo, fexofenadine hydrochloride, and bepotastine besilate. Olopatadine significantly suppressed histamine-induced wheal, flare, and itch, starting 30 minutes after oral administration. Olopatadine was more effective than fexofenadine and bepotastine. None of the drugs studied impaired performance of word processing tasks. These results suggest that olopatadine can suppress skin symptoms caused by histamine soon after administration.